Dietary nitrate supplementation enhances short but not longer duration running time-trial performance - Shannon, O. M.; Barlow, M. J.; Duckworth, L.; Williams, E.; Wort, G.; Woods, D.; Siervo, M.; O`Hara, J. P. (European Journal of Applied Physiology, 2017)
Purpose: This study evaluated the effects of dietary nitrate (NO3 -) supplementation on physiological functioning and exercise performance in trained runners/triathletes conducting short and longer-distance treadmill running time-trials (TT). Method: Eight trained male runners or triathletes completed four exercise performance tests comprising a 10 min warm up followed by either a 1500 or 10,000 m treadmill TT. Exercise performance tests were preceded 3 h before the exercise by supplementation with either 140 ml concentrated nitrate-rich (~12.5 mmol nitrate) (BRJ) or nitrate-deplete (~0.01 mmol nitrate) (PLA) beetroot juice. Results: BRJ supplementation significantly elevated plasma [NO2 -] (P < 0.05). Resting blood pressure and exercise VO2 were not significantly different between BRJ and PLA (P > 0.05). However, post-exercise blood [lactate] was significantly greater in BRJ following the 1500 m TT (6.6 ± 1.2 vs. 6.1 ± 1.5 mM; P < 0.05), but not significantly different between conditions in the 10,000 m TT (P > 0.05). Performance in the 1500 m TT was significantly faster in BRJ vs. PLA (319.6 ± 36.2 vs. 325.7 ± 38.8 s; P < 0.05). Conversely, there was no significant difference in 10,000 m TT performance between conditions (2643.1 ± 324. 1 vs. 2649.9 ± 319.8 s, P > 0.05). Conclusion: Acute BRJ supplementation significantly enhanced 1500 m, but not 10,000 m TT performance. These findings suggest that BRJ might be ergogenic during shorter distance TTs which allow for a high work rate, but not during longer distance TTs, completed at a lower work rate.